Characterization of the 3′ exonuclease subunit DP1 of Methanococcus jannaschii replicative DNA polymerase D - Jokela, Maarit (Oxford University Press, 2004)
The B-subunits associated with the replicative DNA polymerases are conserved from Archaea to humans, whereas the corresponding catalytic subunits are not related. The latter belong to the B and D DNA polymerase families in eukaryotes and archaea, respectively. Sequence analysis places the B-subunits within the calcineurin-like phosphoesterase superfamily. Since residues implicated in metal binding and catalysis are well conserved in archaeal family D DNA polymerases, it has been hypothesized that the B-subunit could be responsible for the 3′-5′ proofreading exonuclease activity of these enzymes. To test this hypothesis we expressed Methanococcus jannaschii DP1 (MjaDP1), the B-subunit of DNA polymerase D, in Escherichia coli, and demonstrate that MjaDP1 functions alone as a moderately active, thermostable, Mn(2+)-dependent 3′-5′ exonuclease. The putative polymerase subunit DP2 is not required. The nuclease activity is strongly reduced by single amino acid mutations in the phosphoesterase domain indicating the requirement of this domain for the activity. MjaDP1 acts as a unidirectional, non-processive exonuclease preferring mispaired nucleotides and single-stranded DNA, suggesting that MjaDP1 functions as the proofreading exonuclease of archaeal family D DNA polymerase.